Color imaging using a system based on 3 diffractive lenses - S. Stepanenko; V. Evdokimova; M. Petrov; R. Skidanov; A. Nikonorov (Компьютерная оптика)
The possibility of essentially reducing the weight and production cost of computer vision systems has led to the publication of a large number of research works dealing with the development of new imaging systems based on diffractive optics. This study proposes a new imaging system composed of three diffractive lenses, with each forming a separate channel of the color RGB image. This approach allows us to significantly narrow the spectral range of each lens, thus significantly reducing the image distortion caused by chromatic aberration inherent in diffractive optics. It shows that this scheme allows us to perform the neural network-aided image reconstruction, providing a significantly improved resulting image quality. The study proposes a false edge level criterion (FEL) for evaluating the neural network-aided reconstruction.